Accountability e contas públicas: uma análise das contas públicas do Poder Executivo pelo Tribunal de Contas dos Municípios do Estado do Pará no período de 2005 a 2014 - OTA, Kleber da Cunha (Universidade Federal do Pará, 2018)
This study has as main objective to analyze the institutional control of public accounts by the Court of Audit Municipalities on the Executive Branch of each Pará Municipality. In this construct, we sought to determine whether the Municipalities Court of Auditors is an effective organ in the control of public accounts, from their decisions, constituting, as a very important accountability mechanism for management of Para public accounts, yet if the Board of Auditors, in its entirety indicated by the ruling political elites demonstrate impartiality in his decisions. To achieve the proposed answers, found by the Theory of accountability, extract the normative theory, guiding the duties of public administration and government, with the purpose and need to protect the citizens of poor bureaucratic conduct. also applying a reflection using the Theory of Regulatory Agencies, facing the external control exercised by the Court of the State of Pará municipalities, as the body attribute assist the City Council. In Project methodology of qualitative research techniques were used from the discussion on documentary research as method of understanding and production of scientific knowledge of decisions rendered by the full Court of the State of Pará municipalities, and at times may realize the application of techniques of quantitative research, contributing to the answers, showing and quantifying evidence or not the actions of the Court of Auditors and may reveal their ideas, opinions and ways of working.